Glucosinolates are produced in trichomes of Arabidopsis thaliana - Frerigmann, Henning; Böttcher, Christoph; Baatout, Dunja; Gigolashvili, Tamara (Frontiers in Plant Science, 2012)
Glucosinolates are important plant secondary metabolites in plant resistance to herbivors, bacteria and fungi, which have been shown to be accumulating in different organs and tissue types at varying concentrations. There are more than 200 glucosinolate species found in order Brassicales and presence of these compounds is well documented on organ-specific but not on cell-specific level. We used UPLC/ESI-QTOF-MS to measure the presence of glucosinolates and qRT-PCR to analyse the expression of glucosinolate biosynthetic and regulatory genes in isolated A. thaliana trichomes. Trichomes of A. thaliana are shown to synthesize chemoprotective aliphatic and indolic glucosinolates, which are known for their biological activities against fungi, bacterial pathogens or herbivores. UPLC/ESI-QTOF-MS analysis of various indolic glucosinolate mutants reveal increased or decreased levels of indolic glucosinolates in trichomes of gain- and loss-of-function mutants correspondingly. Using pMYB51/HIG1-uidA and pMYB28/PMG1/HAG1-uidA reporter plants we demonstrate that production of these important compounds is activated in trichomes of leaves or inflorescences in response to wounding. Since trichoimes represent the first interface in plant-environment interactions, the possible role of glucosinolate containing trichomes in plant defense or signaling is discussed.